Rhetorical Strategies of Counteracting Conspiracy-based Dissent on COVID-19 Vaccines: the #ThinkBeforeSharing Institutional Campaign - Roberta Martina Zagarella; Marco Annoni (Argumentation et Analyse du Discours)
This paper aims to explore how institutions may counteract conspiracy theories using appropriate discursive resources. We use a rhetorical approach to analyze the first European information campaign launched in 2020 to counteract conspiracy theories about COVID-19 vaccines. On this basis, we advance a series of practical recommendations for institutions to counteract conspiracy theories through information campaigns.